(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2023)
The research aimed are to find out the relation between student’s reading performance in blended learning. The researcher found that the relationship between reading performance and digital skills in blended learning is the existence of an educational process that occurs, namely the process of learning and teaching knowledge. By making good use of technology, it could be able to help the level of interest in reading students because most students read more and find out information via cellphones. And in utilizing technology properly it also has such a significant impact on the student learning process. Furthermore, based on the questionnaires that have been distributed, it shows that students are able to channel and improve their reading performance through digital media with mastery of supporting digital skills and only a few of them are not less able to maximize their digital skills and reading performance.